Preliminary exploration of potential biomarkers for heart failure and bipolar disorder: an exploratory study based on bioinformatics - Zhang, Wei; Li, Na (Frontiers in Psychiatry, 2025)
BackgroundIndividuals with bipolar disorder (BD) exhibit a significantly increased risk of cardiovascular disease, yet the specific mechanisms linking heart failure (HF) and BD remain poorly understood. This study aimed to identify common potential diagnostic biomarkers associated with both conditions.MethodsDifferentially expressed genes (DEGs) were analyzed separately in HF (GSE57338) and BD (GSE5389) datasets. Key module genes for each condition were identified through co-expression network analysis and intersected with DEGs to pinpoint candidate genes. Subsequently, a protein-protein interaction (PPI) network, receiver operating characteristic (ROC) analysis, and expression validation were employed to identify potential diagnostic biomarkers. Gene set enrichment analysis (GSEA) and drug predictions were also conducted. Clinical validation of biomarker expression was performed via quantitative polymerase chain reaction (qPCR).ResultsA total of 44 candidate genes were identified as being associated with both HF and BD. Six potential diagnostic biomarkers (UBE2E3, FZD2, EXT1, DCHS1, BMP4, and ALDH1A2) were selected. These biomarkers were predominantly linked to the “cytokine-cytokine receptor interaction” and “ECM receptor interaction” pathways. Additionally, four potential drugs—VANTICTUMAB, RETINOL, HYDROCHLOROTHIAZIDE, and ATENOLOL—were identified as targets for these biomarkers. Expression trends of FZD2, DCHS1, BMP4, and ALDH1A2 validated by qPCR were consistent with dataset findings.ConclusionThis study preliminarily explored the common molecular mechanisms between HF and BD, and identified 6 potential biomarkers for early detection, providing a solid theoretical basis for future research on HF and BD.